Asset Tracking by Religious Court Judges: Ensuring Post-Divorce Child Support - Mansyah, Muh Sutri; Lee, Kirsty; Zudin, Zudin (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
Divorce often causes problems related to the fulfillment of child support, especially when the husband fails to meet his financial obligations. This study aims to analyze the ability of judges to track their husband's assets to ensure child support for divorce victims. The research method used is normative juridical with legislative, case, and conceptual approaches. The results show that although child support is legally guaranteed through the KHI, the Marriage Law, and the Child Protection Law, the implementation of asset tracking still faces technical obstacles, such as the lack of centralized data on the husband's wealth and limited resources of law enforcement. The findings also reveal that judges often rely on the wife’s initiative in submitting evidence of asset ownership, while the mechanism for executing the alimony judgments remains weak. It is important to formulate legal policies regarding the judge's authority to trace the husband's assets as a guarantee of child support. The principle of the best interests of the child must remain the primary consideration in divorce cases. The contribution of this research lies in policy recommendations to revise the Marriage Law and the Issue Supreme Court Regulations concerning the tracking of husbands’ assets in divorce cases.